2016
DOI: 10.1007/s11306-016-1041-6
|View full text |Cite
|
Sign up to set email alerts
|

NMR analysis of the CSF and plasma metabolome of rigorously matched amyotrophic lateral sclerosis, Parkinson’s disease and control subjects

Abstract: Introduction Amyotrophic lateral sclerosis (ALS) and Parkinson's disease (PD) are two severe neurodegenerative disorders for which the disease mechanisms are poorly understood and reliable biomarkers are absent. Objectives To identify metabolite biomarkers for ALS and PD, and to gain insights into which metabolic pathways are involved in disease. Methods Nuclear magnetic resonance (NMR) metabolomics was utilized to characterize the metabolite profiles of cerebrospinal fluid (CSF) and plasma from individuals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 81 publications
(107 reference statements)
4
23
1
Order By: Relevance
“…In a study comparing the metabolome in 22 patients with ALS with 28 controls with other neurologic conditions, the plasma levels of all 3 BCAAs were higher in patients with ALS compared to controls in analyses using nuclear magnetic resonance (NMR) spectroscopy. 11 The results were similar in a study comparing the metabolome in the same cohort of patients and controls using mass spectrometry, but only plasma levels of valine and isoleucine were significantly increased in patients with ALS. 12 Further, one study used NMR to try to identify a diagnostic profile discriminating 95 patients with motor neuron disease from 86 patients with other neurologic diseases and reported that valine and isoleucine measured in the CSF were among the metabolites contributing most to the final diagnostic model.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In a study comparing the metabolome in 22 patients with ALS with 28 controls with other neurologic conditions, the plasma levels of all 3 BCAAs were higher in patients with ALS compared to controls in analyses using nuclear magnetic resonance (NMR) spectroscopy. 11 The results were similar in a study comparing the metabolome in the same cohort of patients and controls using mass spectrometry, but only plasma levels of valine and isoleucine were significantly increased in patients with ALS. 12 Further, one study used NMR to try to identify a diagnostic profile discriminating 95 patients with motor neuron disease from 86 patients with other neurologic diseases and reported that valine and isoleucine measured in the CSF were among the metabolites contributing most to the final diagnostic model.…”
Section: Discussionsupporting
confidence: 55%
“…Previous research on BCAAs and ALS risk is sparse, and no study has previously evaluated the association between prediagnostic plasma levels and disease risk. Some, 11,12,25 but not all, 26,27 studies comparing the metabolome in patients with ALS with controls reported alterations in the metabolism of BCAAs in patients. In a study comparing the metabolome in 22 patients with ALS with 28 controls with other neurologic conditions, the plasma levels of all 3 BCAAs were higher in patients with ALS compared to controls in analyses using nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies did not measure the absolute concentration of amino acids but the relative quantification of many metabolites in individual samples or different groups of samples [3,[6][7][8]10,13]. In another study, CSF absolute concentrations of amino acids were given, but not those of plasma, and therefore it was excluded from the meta-analysis of plasma amino acid levels [5]. Finally, another two studies [4,39] were excluded totally or partially because the results of several amino acids overlapped with the results of other studies of the same group (details in Table S1) [5,40,44] A total of 19 studies reported results of CSF concentrations of at least one amino acid [5,[16][17][18][19][20][22][23][24]26,27,[29][30][31][32][33][34]37,38], and another 18 studies of serum or plasma concentrations of at least one amino acid, in PD patients and controls [11,12,14,16,18,28,[31][32][33]35,36,[39][40]…”
Section: Criteria For Eligibility and Exclusion Of Studies From The Mmentioning
confidence: 99%
“…Classical studies addressing CSF and serum/plasma concentrations of amino acids in PD patients have been largely inconclusive and have shown high variability, which may be related with several factors such as sample size, differences in the handling and storage of samples or in the study methodologies, the lack of a control group or adequate matching between PD patients and controls, and differences in antiparkinsonian therapies [1]. In recent years, there has been an increasing interest in the potential of proteomics/metabolomics multi-analyte profiles both in CSF [3][4][5][6] and/or in serum/plasma [3,[5][6][7][8][9][10][11][12][13][14] to discriminate PD patients from controls.…”
Section: Introductionmentioning
confidence: 99%